Menjelajahi Efisiensi dan Aksesibilitas Godot untuk Pengembang Lokal: Studi Kasus Bilu Mela - Nuswantoro, Fajar (Kartala, 2024)
In the gaming industry, the main challenge faced is the complexity of combining information technology science and film-animation art. These technical and artistic gaps often slow down the production process and reduce the amount of output that can be achieved. This research aims to identify simpler and cheaper alternative production methods to increase the quantity of game production without sacrificing quality. To achieve this goal, a series of hands-on game creation experiments were carried out by researcher. This method is expected to provide an idea of game engine easiness and how helpful a community when the researcher encounter difficulties in making games. The results of this research show that the use of Godot in game production has a significant impact on production efficiency. This more efficient process has the potential to increase the amount of game production in Indonesia, providing opportunities for the local games industry to develop and compete in the global market. Thus, this research not only contributes to academic knowledge, but also has significant practical implications for the gaming industry. This discovery is expected to encourage more innovation and aesthetics in the application of artificial intelligence in various aspects of game production. Keywords: efficiency, games, media transfer, godot, animation